Musculoskeletal Pain and Interest in Meditation and Yoga in Home Health Aides: Evidence From the Home Health Occupations Musculoskeletal Examinations (HHOME) Study. (March 2018) - Shnayder, Michelle M.; Brannan, Debi; Murphy, Lauren A.; Asfour, Lila S.; Hecht, Eric M.; Lee, David J.; Caban-Martinez, Alberto J.
Abstract : Home healthcare aides (HHAs) are a growing U.S. workforce highly susceptible to workplace stressors and musculoskeletal pain. In the present study we: 1) examine the association of musculoskeletal pain to life satisfaction and emotional exhaustion; and 2) characterize interest in meditation and yoga in a sample of HHAs. A nonprobabilistic sample of HHAs employed at home healthcare agencies in Florida, Massachusetts, and Oregon (n = 285 total) completed a self-administered questionnaire with standard survey measures on musculoskeletal pain location, duration, and severity; life satisfaction; emotional exhaustion; and interest in meditation techniques and yoga. Among HHAs responding, 48.4% reported pain in the last 7 days and 46.6% reported pain in the last 3 months. Home healthcare aides who reported current pain and chronic pain had a significant (P < .05) decrease in satisfaction with life score and a significant increase in emotional exhaustion score. The majority of HHAs reported an interest in learning about the benefits (65.6%) and practice (66.4%) of meditation and a willingness to participate in a yoga class (59.2%) or stress management meeting (59.1%). The HHAs reported both acute and chronic musculoskeletal pain that was correlated with lower life satisfaction and greater emotional exhaustion. More efforts are needed to reduce the sources of injury and emotional exhaustion.